أثر النشاط الرياضي الترويحي على الجانب الاجتماعي العاطفي لدي الأطفال المتخلّفين عقليا في المراكز التربوية - بن علي, عدّة (Tamayoz, 2019)
إن موضوع بحثنا هذا يدور حول محور أساسي هو بيان أهمية النشاط الرياضي الترويحي للأطفال المتخلفين عقليا في نمو المجال الاجتماعي العاطفي، ولتحقيق ذلك ، و بما ان دراستنا ستتناول النشاط الرياضي الترويحي لدى الاطفال المتخلفين عقليا تخلفا بسيطا في المراكز التربوية , و اهميته لهذه الفئة من الناحية الاجتماعية العاطفية , فان ذلك يتطلب استعمال المنهج الوصفي بالطريقة المسحية دراسة مقارنة ، واداة الدراسة كانت الاستبيان . تم اختيار عينة البحث من الأطفال المتخلفين عقليا , تخلفا بسيطا في كل من جمعية مساعدة الأطفال المتخلفين عقليا الكائن ببوشقيف و المركز التربوي الكائن بحي التفاح بلدية تيارت ولاية تيارت , حيث بلغ عدد الاطفال المتخلفون عقليا تخلفا بسيطا 25 طفلا بمركز بوشقيف , و 20 طفلا بمركز تيارت . Abstract : The topic of this search is about the essential pivot is a statement of the importance of recreational sports activity for mentally retarded children in the growth of the social, emotional, to achieve this, including that our study will focus on the recreational sports activity to mentally retarded children backward simple educational centers, and its importance for this category in the social, emotional, requires the use of the descriptive approach the way surveys of comparative study, and a tool of the study was the questionnaire. The research sample was selected from the mentally retarded children, simple lag in each of the Assistance Association of mentally retarded children object bouchekif and educational center located in the municipality of tiaret Apple Tiart, where the number of the Mentally subnormal children simple lag 25 children the status of nouchekif, and 20 children the status of tiaret.